2016
DOI: 10.1002/1873-3468.12342
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 adaptor proteins, TAB2 and TAB3, link the signalosome to B‐cell receptor‐induced IKK activation

Abstract: Edited by Wilfried EllmeierTransforming growth factor-b-activated kinase (TAK)1-binding proteins (TAB) activate nuclear factor-jB by linking TAK1 to signaling molecules. We investigated the mechanisms underlying B-cell receptor (BCR) signaling in TAB2-and TAB3-deficient and TAB3 domain deletion mutant DT40 B cell lines. Loss of TAB2 and TAB3 abolished BCR-induced inhibitor of jB kinase (IKK) activation and TAK1 binding to caspase recruitment domain membrane-associated guanylate kinase protein (CARMA)1. Deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Together with the role TAK1 plays in the MAPK pathway, it is also well documented as important in mediating NF‐κB activity in various cell types including HeLa, HEK293T, ex vivo neurons, microglia cells, and B and T lymphocytes, to name a few 24 , 45 48–52 ; however, the precise nature of the TAK1 role has been a challenge to dissect at times. In B cell receptor (BCR) signaling, based on differential knockout models, the kinase activity of TAK1 was shown to be dispensable on the one hand, 45 while others later demonstrated that the physical protein, likely via its interactions 53 (e.g., TAB2 and TAB3) were critical 52 . Evidence to support the conservation of this role in the context of allergen‐challenged mast cells has not been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the role TAK1 plays in the MAPK pathway, it is also well documented as important in mediating NF‐κB activity in various cell types including HeLa, HEK293T, ex vivo neurons, microglia cells, and B and T lymphocytes, to name a few 24 , 45 48–52 ; however, the precise nature of the TAK1 role has been a challenge to dissect at times. In B cell receptor (BCR) signaling, based on differential knockout models, the kinase activity of TAK1 was shown to be dispensable on the one hand, 45 while others later demonstrated that the physical protein, likely via its interactions 53 (e.g., TAB2 and TAB3) were critical 52 . Evidence to support the conservation of this role in the context of allergen‐challenged mast cells has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…In B cell receptor (BCR) signaling, based on differential knockout models, the kinase activity of TAK1 was shown to be dispensable on the one hand, 45 while others later demonstrated that the physical protein, likely via its interactions 53 (e.g., TAB2 and TAB3) were critical. 52 Evidence to support the conservation of this role in the context of allergen-challenged mast cells has not been documented. Here, we sought to determine whether TAK1 activity-dependent NF-B signaling function would be conserved in mast cells, as a molecule with dual MAPK and NF-B regulatory function might carry substantial impact on the production of mast cell inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…data]. TAB3 is an adaptor molecule that, in combination with protein kinase TAK1, phosphorylates the subunit of NFκB, IκBα/β and leads to NFκB activation [23, 24]. Data on the potential role of TAB3 in the context of allergy is limited.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation may be that patients with allergies have a lower constitutive TAB3 expression reflecting their atopic status. Studies described in cancer research showed TAB3 as one of the important molecules in a cascade of genes forming the NFκB activation pathway [24, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies revealed the biological functions of TAB3 in different cells (Mendoza et al, 2008;Min et al, 2012;Hu et al, 2015;Shinohara et al, 2016). Of these properties, apoptosis induction and proliferation inhibition by TAB3 have garnered attention from researchers.…”
Section: Discussionmentioning
confidence: 99%